Methane storage system and preparation method thereof, and preparation method of methane hydrate
By using a layered porous material and anionic surfactant aqueous solution during the growth of methane hydrate, the problems of slow growth rate and low gas storage rate of methane hydrate are solved, and a more efficient methane gas storage effect is achieved.
Patent Information
- Application Number
- CN202510222867.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-27
- Publication Date
- 2025-04-25
AI Technical Summary
The slow growth rate of methane hydrates and low gas storage rate hinder the application of hydrate technology.
A methane storage system is adopted that includes a sheet-like porous material and an aqueous solution containing anionic surfactant. By mixing the sheet-like porous material with the aqueous solution, it provides rich nucleation sites and good heat transfer capabilities.
The gas storage capacity and gas storage efficiency of methane hydrate are improved, the nucleation induction time of methane hydrate is shortened, and the methane gas storage capacity is increased.
Smart Images

Figure CN119875583A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of hydrate preparation, and in particular to a methane storage system and a preparation method thereof, and a preparation method of methane hydrate. Background Art
[0002] Methane hydrate mainly forms a framework through the hydrogen bonding of water molecules, allowing methane molecules to exist in the framework, thus forming a crystalline compound. Therefore, methane storage and transportation using methane hydrate as a medium has considerable development prospects. However, during the growth of methane hydrate, there is mass transfer resistance between gas molecules and water phase, and there are fewer nucleation sites, which leads to slow hydrate growth rate and low gas storage rate, hindering the application of hydrate technology.
[0003] Anionic surfactants, such as sodium dodecyl sulfate (SDS), can enhance the solubility of gas in the liquid phase and reduce surface tension at the gas-liquid interface. Adding anionic surfactants during the growth of methane hydrates is beneficial to improving the gas-liquid mass transfer capacity, but it is still difficult to provide more effective nucleation sites for the growth of hydrates. Therefore, the growth rate and gas storage rate of methane hydrates still need to be improved. Summary of the invention
[0004] In view of this, the present application provides a methane storage system and a preparation method and application thereof to solve at least one of the above problems.
[0005] To achieve the above objectives, in a first aspect, the present application provides a methane storage system, comprising a lamellar porous material and an aqueous solution containing anionic surfactants, wherein at least a portion of the lamellar porous material is mixed in the aqueous solution.
[0006] In some possible implementations, the anionic surfactant includes sodium dodecyl sulfate, and the lamellar porous material includes lamellar expanded graphite.
[0007] In some possible implementations, the thickness of the lamellar expanded graphite is 0.6 mm to 1.0 mm.
[0008] In some possible implementations, in the methane storage system, an angle between a plane defined by the lamellar expanded graphite and a direction where a liquid surface of the aqueous solution is located is 60° to 90°.
[0009] In some possible implementations, the mass fraction of the lamellar expanded graphite in the methane storage system is 3.2% to 21.3%.
[0010] In a second aspect, the present application provides a method for preparing the above-mentioned methane storage system, comprising: providing a lamellar porous material; mixing the lamellar porous material, anionic surfactant and water to obtain the methane storage system.
[0011] In some possible implementations, based on the total mass of the lamellar porous material and the water, the mass fraction of the lamellar porous material is 3.2% to 21.3%.
[0012] In some possible implementations, the concentration of the anionic surfactant is 50 ppm to 500 ppm.
[0013] In some possible implementations, the lamellar porous material includes lamellar expanded graphite, which is obtained by subjecting expanded graphite to a sheeting process at 5 MPa to 30 MPa.
[0014] In a third aspect, the present application also provides a method for preparing methane hydrate, which comprises: placing the above-mentioned methane storage system or the methane storage system prepared by the above-mentioned preparation method in a reaction container; injecting methane into the reaction container and reacting to obtain the methane hydrate.
[0015] The methane storage system of the present application, while the anionic surfactant improves the gas-liquid mass transfer capacity, combines the structure of the lamellar porous material to provide abundant nucleation sites and good heat transfer capacity for the formation of methane hydrates, and provides support for the hydrogen bond framework of water molecules, which is beneficial to improving the gas storage capacity and efficiency of methane hydrates. On the basis of the porous material providing a loose pore structure, the use of lamellar porous materials (such as lamellar expanded graphite) is beneficial to the wall climbing effect of the anionic surfactant, which is beneficial to the more efficient use of the nucleation sites of the hydrate, thereby accelerating the growth rate of methane hydrates, further shortening the nucleation induction time of methane hydrates and increasing the methane gas storage capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a plane scanning electron microscope image of the lamellar expanded graphite provided in Example 1 of the present application.
[0017] Figure 2 This is a cross-sectional scanning electron microscope image of the lamellar expanded graphite provided in Example 1 of the present application.
[0018] Figure 3 A graph showing the change in gas storage capacity over time of the methane storage system provided in Example 1 and Comparative Example 1 of the present application. DETAILED DESCRIPTION
[0019] The embodiments of the present application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application; it should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by technicians in the technical field of the present application; in the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other; many specific details are elaborated in the following description to facilitate a full understanding of the present application, and the described embodiments are only part of the embodiments of the present application, not all of the embodiments.
[0020] Since anionic surfactants cannot theoretically provide more effective nucleation sites for the growth of methane hydrates in the process of promoting the formation of methane hydrates, the methane storage capacity is still limited. The present application improves the existing methane hydrate formation promoter to shorten the formation time of methane hydrates or increase the methane storage capacity.
[0021] Based on this, one embodiment of the present application provides a methane storage system, including a lamellar porous material and an aqueous solution containing anionic surfactants, at least part of the lamellar porous material is mixed in the aqueous solution.
[0022] While the anionic surfactant improves the gas-liquid mass transfer capacity, the present application combines the structure of the lamellar porous material to provide abundant nucleation sites and good heat transfer capacity for the formation of methane hydrates, and provides support for the hydrogen bond framework of water molecules, which is beneficial to improving the gas storage capacity and efficiency of methane hydrates. On the basis of the porous material providing a loose pore structure, the use of lamellar porous materials (such as lamellar expanded graphite) is beneficial to achieve a more efficient use of nucleation sites with the help of the lamellar structure, and is also beneficial for the infiltrated anionic surfactant to better play a role in promoting the growth rate of hydrates, thereby further shortening the nucleation induction time of methane hydrates and increasing the methane gas storage capacity.
[0023] It should be noted that the present application also found that when at least part of the lamellar porous material is infiltrated with anionic surfactants, the potential detected by the liquid in the system decreases, and methane hydrates begin to grow at the infiltrated lamellar porous material and can gradually spread to the uninfiltrated lamellar porous material. Therefore, in the present application, by making part of the lamellar porous material infiltrated with anionic surfactants, the growth of methane hydrates can be promoted, which also shows that the methane storage system of the present application has a high gas storage efficiency.
[0024] In some embodiments, the anionic surfactant includes sodium dodecyl sulfate, and the lamellar porous material includes lamellar expanded graphite.
[0025] In some embodiments, the thickness of the lamellar expanded graphite is 0.6 mm to 1.0 mm. For example, the thickness of the lamellar expanded graphite can be 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, or any value within the range formed by any two of the above values. Controlling the thickness of the lamellar expanded graphite within the above range is conducive to forming a more stable lamellar porous structure, improving the support effect on the hydrogen bond framework of water molecules, and facilitating more efficient utilization of nucleation sites.
[0026] In some embodiments, in the methane storage system, the angle between the plane defined by the lamellar expanded graphite and the direction of the liquid surface of the aqueous solution is 60° to 90°. It can be understood that the "plane defined by the lamellar expanded graphite" refers to the plane where the graphite molecular flakes are located at the microscopic level. For example, the above angle can be 60°, 70°, 80°, 90° or any value within the range formed by any two of the above values. The angle between the direction of the lamellae of the lamellar expanded graphite in the methane storage system and the direction of the immersion liquid surface is within the above range, which can promote the formation of methane hydrates and increase the gas storage capacity.
[0027] In some embodiments, the mass fraction of the lamellar expanded graphite in the methane storage system is 3.2% to 21.3%. For example, the mass fraction of the lamellar expanded graphite in the methane storage system can be 3.2%, 9.2%, 14.5%, 21.3%, or any value within the range formed by any two of the above values. Controlling the mass fraction of the lamellar expanded graphite in the methane storage system within the above range is conducive to obtaining a stable lamellar porous structure, improving the support effect on the hydrogen bond framework of water molecules, and facilitating more efficient utilization of nucleation sites.
[0028] An embodiment of the present application further provides a method for preparing the above-mentioned methane storage system, comprising: Step 1: providing a lamellar porous material.
[0029] In some embodiments, the lamellar porous material includes lamellar expanded graphite, which is obtained by pressing expanded graphite at 5 MPa to 30 MPa. For example, the expanded graphite can be pressed at 5 MPa, 10 MPa, 15 MPa, 20 MPa, 25 MPa, 30 MPa or any value within the range of any two of the above values. The lamellar expanded graphite obtained by pressing the expanded graphite is conducive to achieving a more efficient utilization of nucleation sites through the lamellar structure, and is also conducive to the infiltrated anionic surfactant to better play a role in promoting the growth rate of hydrates, thereby further shortening the nucleation induction time of methane hydrates and increasing the methane gas storage capacity.
[0030] In some embodiments, expanded graphite can be obtained by heat treating a precursor of expanded graphite (such as graphite powder) at 400° C. to 700° C. For example, a precursor of expanded graphite (such as graphite powder) can be heat treated at 400° C., 450° C., 500° C., 550° C., 600° C., 650° C., 700° C., or at any temperature within the range formed by any two of the above values to obtain expanded graphite.
[0031] Step 2: Mix the lamellar porous material, anionic surfactant and water to obtain the methane storage system. When at least part of the lamellar porous material is infiltrated by the anionic surfactant, the potential detected by the liquid in the system decreases, and methane hydrates begin to grow at the infiltrated lamellar porous material and can gradually spread to the uninfiltrated lamellar porous material. Therefore, in the present application, by infiltrating part of the lamellar porous material with anionic surfactant, the growth of methane hydrates can be promoted, which also shows that the methane storage system of the present application has a high gas storage efficiency.
[0032] In some embodiments, based on the total mass of the lamellar porous material and the water, the mass fraction of the lamellar porous material is 3.2% to 21.3%. For example, the mass fraction of the lamellar porous material in water can be 3.2%, 9.2%, 14.5%, 21.3%, or any value within the range formed by any two of the above values.
[0033] In some embodiments, the concentration of the anionic surfactant is 50 ppm to 500 ppm. For example, the concentration of the anionic surfactant can be 50 ppm, 100 ppm, 200 ppm, 300 ppm, 400 ppm, 500 ppm, or any value within the range formed by any two of the above values.
[0034] Controlling the contents of the lamellar porous material, the anionic surfactant and water within the above ranges is beneficial to controlling the mass proportion of the lamellar porous material (such as lamellar expanded graphite) in the resulting methane storage system, thereby helping to control the structural stability of the lamellar porous material, and is beneficial to controlling the degree of wetting of the anionic surfactant in the resulting methane storage system, so that the lamellar porous material combined with the anionic surfactant can better play a role in promoting the formation of methane hydrates and increasing the gas storage capacity.
[0035] An embodiment of the present application also provides a method for preparing methane hydrate, the preparation method comprising: Step 1: placing the methane storage system mentioned above or the methane storage system prepared by the above preparation method in a reaction container.
[0036] Step 2: injecting methane into the reaction container and reacting to obtain the methane hydrate.
[0037] During the above methane injection process, when the pressure in the reaction vessel continues to drop and the temperature continues to rise, it indicates that methane hydrate is in the process of formation. When the pressure and temperature in the reaction vessel return to stability, it indicates that the methane hydrate formation process is over. The stainless steel high-pressure reactor is taken out and opened to obtain methane hydrate. Methane hydrate begins to grow on the surface of the lamellar porous material and can gradually spread and grow in the reaction vessel.
[0038] The scheme of the present application will be explained below in conjunction with the embodiments. Those skilled in the art will understand that the following examples are only used to explain the present application and cannot be construed as limiting the present application. Unless otherwise stated, the reagents, software and instruments not specifically stated in the following embodiments are all conventional commercial products or open source.
[0039] Embodiment 1: A method for preparing methane hydrate, comprising: (1) Preparation of lamellar expanded graphite: Graphite powder was used as raw material and sintered in a muffle furnace at 700 °C for 2 min to obtain an expanded powder material. 100 g of the expanded powder material was taken and a tablet press was used to prepare lamellar expanded graphite with a thickness of 1.0 mm at a pressure of 20 MPa.
[0040] (2) Preparation of methane storage system: SDS was added to a certain amount of water to prepare a 300 ppm SDS aqueous solution, which was then completely dissolved by ultrasonic treatment at room temperature for 20 min. The flaky expanded graphite obtained in (1) was cut into discs with a diameter of 5 cm, and the flaky expanded graphite and the above-mentioned SDS aqueous solution were mixed in a reactor so that the mass fraction of the flaky expanded graphite in water was 21.3%, and the plane defined by the flaky expanded graphite was perpendicular to the liquid surface of the SDS aqueous solution.
[0041] (3) Methane hydrate reaction: The methane storage system prepared in (2) was transferred to a stainless steel autoclave with a volume of 140 mL. The stainless steel autoclave was placed in a water bath at a temperature of 2 °C. The real-time temperature and pressure of the stainless steel autoclave were recorded by a temperature sensor and a pressure sensor, respectively. After the temperature reading was constant at 2 °C, the high-purity methane gas cylinder was opened and methane gas was injected into the stainless steel autoclave until the pressure of the stainless steel autoclave reached 8 MPa. The gas cylinder was then closed. When the pressure continued to drop and the temperature continued to rise, it indicated that methane hydrate was in the process of formation. When the pressure and temperature returned to stability and no longer changed, it indicated that the methane hydrate formation process was completed. The stainless steel autoclave was taken out and opened to obtain methane hydrate.
[0042] Example 2: The difference from Example 1 is that (1) the firing conditions in the muffle furnace are adjusted to 700°C for 2 min, and the tablet press pressure is adjusted to 30 MPa, to obtain lamellar expanded graphite with a thickness of 0.6 mm.
[0043] Example 3: The difference from Example 1 is that (1) the firing conditions in the muffle furnace are adjusted to 600°C for 2 min, and the tablet press pressure is adjusted to 20 MPa, to obtain lamellar expanded graphite with a thickness of 0.8 mm.
[0044] Example 4: The difference from Example 1 is that the mass fraction of the lamellar expanded graphite in water in (2) is adjusted to 3.2%.
[0045] Example 5: The difference from Example 1 is that the mass fraction of the lamellar expanded graphite in water in (2) is adjusted to 9.2%.
[0046] Example 6: The difference from Example 1 is that the mass fraction of the lamellar expanded graphite in water in (2) is adjusted to 14.5%.
[0047] Example 7: The difference from Example 1 is that the concentration of SDS in (2) is adjusted to 50 ppm.
[0048] Comparative Example 1: The difference from Example 1 is that (1) after the graphite powder is sintered and expanded, no tableting treatment is performed.
[0049] The present application observes the structure of the flaky expanded graphite in Example 1 by scanning electron microscopy, including immersing the pressed sample in liquid nitrogen for 1 min, and quickly cutting it in liquid nitrogen, sticking the cross section upward on the sample stage (the cross section faces the camera), and spraying gold on the cut flaky expanded graphite, and then observing it by scanning electron microscopy, please refer to Figure 1 and Figure 2 The lamellar expanded graphite in Example 1 has a loose and porous lamellar structure.
[0050] The present application also uses a nitrogen adsorption-desorption instrument to measure the specific surface area of the lamellar expanded graphite before and after the reaction with methane, thereby characterizing the stability of the lamellar expanded graphite in the reaction system. The results show that the BET specific surface area of the lamellar expanded graphite is 21 m 2 / g, the specific surface area of methane hydrate after formation can still be maintained at 21 m 2 / g, indicating that in the methane storage system of the present application, the lamellar expanded graphite has good stability, which is beneficial to provide abundant nucleation sites and good heat transfer ability in the process of methane hydrate formation, and provide support for the hydrogen bond framework of water molecules.
[0051] The present application also observes the formation process of methane hydrate through a visualized reactor, and the observation results show that the methane hydrate begins to grow at the lamellar porous material and can gradually spread to the entire reactor.
[0052] The present application also tests the gas storage capacity of the methane storage system, including using helium to calibrate the actual volume V0 of the methane storage system and the actual methane storage capacity V1 of the methane storage system: (1) Place the prepared methane storage system into a high-pressure reactor, let it stand, seal it, and place it in a 2°C water bath to cool it down; (2) When the temperature of the high-pressure reactor drops to the set temperature and no longer changes, open the helium cylinder to inflate the high-pressure reactor. After inflating to the set pressure, close the helium cylinder, measure the volume of the methane storage system, and then slowly discharge the helium to obtain V0; (3) According to the pressure gauge count of the high-purity methane gas cylinder used, the methane V1 that can be stored in the above-mentioned embodiments and comparative examples is obtained.
[0053] The present application also obtains the induction time of methane hydrate in the above-mentioned embodiments and comparative examples by timing the methane reaction process. Please refer to Table 1 for the test results.
[0054] Table 1. Test results of gas storage capacity and induction time of methane hydrate of methane storage systems of Examples 1-7 and Comparative Example 1 of the present application The methane storage system of Examples 1-7 of the present application includes anionic surfactants, lamellar porous materials and water. While the anionic surfactant improves the gas-liquid mass transfer capacity, combined with the structure of the lamellar porous material, it provides abundant nucleation sites and good heat transfer capacity for the formation of methane hydrates, provides support for the hydrogen bond framework of water molecules, and is conducive to improving the gas storage capacity and efficiency of methane hydrates. The use of lamellar porous materials (such as lamellar expanded graphite) is conducive to achieving more efficient utilization of nucleation sites with the help of lamellar structures, and is also conducive to the infiltrated anionic surfactant to better play a role in promoting the growth rate of hydrates, thereby further shortening the nucleation induction time of methane hydrates and increasing the methane gas storage capacity.
[0055] Compared with Example 1, Comparative Example 1 uses expanded graphite without tableting. Although the loose porous structure improves the formation of methane hydrate to a certain extent, the extent to which it promotes growth and increases gas storage capacity is limited. Figure 3 , taking 300 ppm SDS as a promoter as a reference, the methane content and the formation rate of the methane hydrate obtained in Comparative Example 1 are not as good as those in the examples of the present application.
[0056] The above implementation modes are only used to illustrate the technical solutions of the present application and are not intended to limit the present application. Although the present application has been described in detail with reference to the above preferred implementation modes, a person skilled in the art should understand that the technical solutions of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present application.
Claims
1. A methane storage system, characterized in that: The methane storage system comprises a lamellar porous material and an aqueous solution containing anionic surfactant, wherein at least a part of the lamellar porous material is mixed in the aqueous solution.
2. The methane storage system according to claim 1, characterized in that: The anionic surfactant includes sodium dodecyl sulfate, and the lamellar porous material includes lamellar expanded graphite.
3. The methane storage system according to claim 2, characterized in that: The thickness of the lamellar expanded graphite is 0.6 mm to 1.0 mm.
4. The methane storage system according to claim 2, characterized in that: In the methane storage system, the angle between the plane defined by the lamellar expanded graphite and the direction of the liquid surface of the aqueous solution is 60° to 90°.
5. The methane storage system according to claim 2, characterized in that: The mass fraction of the lamellar expanded graphite in the methane storage system is 3.2% to 21.3%.
6. A method for preparing a methane storage system according to claim 1, characterized in that: include: Providing a porous material in a lamellar form; The lamellar porous material, anionic surfactant and water are mixed to obtain the methane storage system.
7. The preparation method according to claim 6, characterized in that: Based on the total mass of the lamellar porous material and the water, the mass fraction of the lamellar porous material is 3.2% to 21.3%.
8. The preparation method according to claim 6, characterized in that The concentration of the anionic surfactant is 50 ppm to 500 ppm.
9. The preparation method according to claim 6, characterized in that The lamellar porous material includes lamellar expanded graphite, which is obtained by subjecting expanded graphite to a tableting process at 5 MPa to 30 MPa.
10. A method for preparing methane hydrate, characterized in that: The preparation method comprises: Placing the methane storage system according to any one of claims 1 to 5 in a reaction vessel; Methane is injected into the reaction container and reacted to obtain the methane hydrate.
Citation Information
Patent Citations
Pressure vessel for CO2 displacement and pressure reduction combined mining of hydrates
CN104088611A
Preparation method of highly dispersed natural gas hydrate sol additive
CN109022075A
Methane gas storage method
JP2000120995A